Cyclohexenyl-containing blue luminescent compound and organic electroluminescent device containing same
Through the introduction of cycloidnonine structures on the boron -Nuclear skeleton, combined with AIE, TADF, and multiple resonance effects, the problem of insufficient ACQ effect and stability in the doped system in the doped system of Blu -ray OLED materials has been solved. OLED device.
Patent Information
- Application Number
- CN202411448926.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing blue light OLED materials have a concentration quenching effect (ACQ effect) in the doping system, resulting in a reduced fluorescence quantum efficiency and insufficient material stability, affecting device life.
By introducing a substituted cyclohexenyl structure into the boron-nitrogen core skeleton, combined with the aggregation-induced emission (AIE) effect, the thermally activated delayed fluorescence (TADF) effect and the multiple resonance effect, a special steric distortion structure is formed. Improve material stability and efficiency.
Effectively block the impact of AIE effect structure fragments on the core area of the mother nuclear lighting, improve the electrophties of the blue light material in the doping system, significantly improve the efficiency of the device, and maintain a long life of the device.
Smart Images

Figure CN119330998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OLED, and specifically comprises a blue light-emitting compound containing a cyclohexenyl group and an organic electroluminescent device containing the same. Background Art
[0002] The AIE effect originated in 2001. These molecules have a very twisted propeller configuration, which is significantly different from pyrene, which has a planar structure. In solution, the outer benzene ring can rotate around the central silole ring, so the energy of the excited state is dissipated in the form of non-radiative transitions, making the molecule non-luminescent. When aggregated, the restriction of intramolecular rotation is achieved with the help of intermolecular and hydrophobic interactions, resulting in strong emission. Since the above-mentioned luminescence phenomenon is induced by aggregation, Professor Tang Benzhong first proposed the scientific concept of "aggregation-induced emission" (AIE). The discovery and research of the aggregation-induced emission phenomenon has promoted the improvement of the luminescence ability of luminescent materials in the aggregated state, but the application of such materials in doping systems is still relatively limited. Tetraphenylethylene (TPE) is a typical small molecule with AIE effect and is often used as a skeleton to construct AIE compounds. However, there has been no report on its application in MR-TADF materials. This is because the olefin group is a relatively active group and may deteriorate and decompose during the sublimation and evaporation process of the material. Therefore, although there is a patent claiming that the substituent in the BD structure can be an olefin group, the relevant structure and related device evaluation results have not been disclosed.
[0003] TADF materials utilize the small difference between triplet energy and singlet energy. Through reverse intersystem crossing of triplet excitons, the luminescent material has more singlet excitons, thereby achieving 100% utilization of excitons. However, the lifetime of triplet excitons is much longer than that of singlet excitons. In addition to reverse intersystem crossing, triplet excitons can also be quenched and inactivated through internal conversion, vibrational relaxation, non-radiative transitions, and even accelerate the decomposition and degradation of materials, which makes this type of material have serious efficiency roll-off problems; in 2020, Hyung Jong Kim reported on combining the AIE effect with TADF, using structures such as carbazole and aromatic amine to introduce into the boron-oxygen structure, but the AIE effect of the aromatic amine structure is limited, and the boron-oxygen structure also has problems such as a wide half-width.
[0004] MR-TADF, based on TADF materials, limits the transition process to the atomic region level through multiple resonance effects, which is beneficial to spectral sharpening and reducing the half-peak width. However, this type of material has a more serious concentration quenching effect (ACQ effect) due to the larger plane of the resonant parent nucleus, so it is often used in doping systems. Current research mainly focuses on reducing the polarity of the material and intermolecular interactions by using small molecule alkyl groups such as methyl and tert-butyl groups on the periphery of the molecular structure. However, the doping concentration of this type of boron nitrogen material is still greatly limited. Usually, the doping concentration in the device does not exceed 5%, and the higher the concentration, the lower the fluorescence quantum efficiency of a single molecule, which limits the further improvement of the efficiency of blue light devices.
[0005] In recent years, studies have found that the energy transfer mechanism can be further improved by introducing sensitizing materials. That is, by adding a phosphorescent material or TADF material with high exciton utilization rate as a sensitizer between the host and the guest, the energy transfer function between the host and the guest can be improved, thereby improving the efficiency. However, there is also a certain ACQ effect between the sensitizing material and the doping material, which limits the efficiency improvement.
[0006] The applicant had previously reduced the impact of the concentration quenching effect by expanding the alkyl size and increasing the steric structure, but compared to red and green light materials, it is still necessary to develop blue light materials with low driving voltage, high luminous efficiency and long device life. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a blue light-emitting compound containing a cyclohexenyl group and an organic electroluminescent device containing the same.
[0008] To achieve the above objectives, the technical solutions adopted by the present invention include:
[0009] The first aspect of the present invention provides a blue light-emitting compound containing a cyclohexenyl group, wherein the blue light-emitting compound is as shown in Formula I;
[0010]
[0011] wherein Ring A represents any one of a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, and a substituted or unsubstituted heteroaryl group having 5 to 30 carbon atoms;
[0012] R1-R5 each independently represents any one of a methyl group, an ethyl group, a propyl group, an isopropyl group, a tert-butyl group, a cycloalkyl group, a cyclohexenyl group, a diamino group, a cyclohexenyl-substituted diamino group or a carbazole group, and at least one of R1-R5 represents a cyclohexenyl structure shown in one of A1 to A3 below, and adjacent R2 groups may be bonded to each other via a linking group or a single bond to form an aromatic ring or a condensed ring;
[0013]
[0014] R6 represents hydrogen or methyl;
[0015] L1-L3 each independently represent any one of a single bond, a substituted or unsubstituted arylene group, a substituted or unsubstituted arylene group connected in a ring, and a substituted or unsubstituted arylene group connected in a heterocyclic ring;
[0016] m, n, o, p, q each independently represent 0, 1, 2 or 3. When m, n, o, p, q represent 2 or 3, R1-R5 may be the same or different;
[0017] In Formula I, any hydrogen may be replaced by deuterium, and any nitrogen may be replaced by 15 N substitution, any sulfur can be 33 S. 34 S or 36 S substitution, any oxygen can be 17 O or 18 O substitution, any carbon can be 13 C substitution, any boron can be 11 B replaced.
[0018] Furthermore, at least one of R3 and R5 is selected from one of the cyclohexenyl structures shown in A1 to A3.
[0019] Furthermore, the blue light-emitting compound is selected from the structure shown in Formula II or Formula III:
[0020]
[0021] Furthermore, the compound represented by Formula II is selected from the structure represented by one of Formula II-1 to Formula II-7:
[0022]
[0023]
[0024] m1, m5, and m6 each independently represent an integer from 0 to 5, and m2, m3, m4, and m7 each independently represent an integer from 0 to 8;
[0025] n1, n2, n5, n6, and n7 each independently represent an integer from 0 to 5, and n3 and n4 each independently represent an integer from 0 to 8;
[0026] R 11 , R 21 , R4 each independently represents hydrogen or an alkyl group having 1 to 5 carbon atoms; at least one of R3 and R5 is a cyclohexenyl structure represented by one of A1 to A3.
[0027] Furthermore, the R 11 , R 21Represents hydrogen.
[0028] Furthermore, when there are more carbazoles in the structure, the synergistic effect of the AIE effect of carbazole and aromatic amine itself and the AIE effect of cyclohexene is more obvious, so formula II-3 and II-4 are superior to other general structures.
[0029] Furthermore, the compound represented by formula III is selected from the structure represented by one of formulas III-1 to III-4:
[0030]
[0031] R7 and R8 each independently represent any one of an alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, a substituted or unsubstituted cyclohexenyl group, and a substituted or unsubstituted dibenzofuranyl group;
[0032] n8 represents an integer of 0-4, and is preferably 1.
[0033] Further, the arylene group is selected from any one of phenylene, biphenylene, and terphenylene;
[0034] The arylene group connected in a ring is selected from any one of fluorenylene and spirofluorenylene;
[0035] The arylene group connected with the heterocyclic ring is selected from any one of dibenzofuranyl and diarylamine.
[0036] Furthermore, the blue light-emitting compound is selected from one of the following structures:
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049] The second aspect of the present invention provides an organic electroluminescent device, which includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode arranged in sequence on a substrate; wherein the light-emitting layer includes one or more blue light-emitting compounds as described above.
[0050] Furthermore, the light-emitting layer includes a host material and a guest material, wherein the guest material includes one or more of the blue light-emitting compounds described above.
[0051] Beneficial effects of the present invention:
[0052] The present invention can organically combine the aggregation-induced emission effect, thermally activated delayed fluorescence effect, multiple resonance effect and peripheral grafting dispersion effect by introducing a substitutable cyclohexenyl structure on the boron nitrogen parent core skeleton, and form a special steric distorted structure by combining the alkenyl with the cycloalkyl fragment structure, which effectively blocks the influence of the AIE effect structure fragment on the luminescent core area of the parent core, and avoids the influence of similar aromatic amine AIE fragments on the luminescent peak position of the parent core structure; the introduction of alkenes into the substitutable cycloalkyl structure also improves the stability of the alkenyl to a certain extent, so that the material can significantly improve the efficiency while avoiding serious attenuation of life. This fragment with both AIE effect and peripheral grafting effect is introduced into a boron nitrogen mother core with MR-TADF effect to form a boron nitrogen doped material containing a cyclohexenyl fragment that can be used in a doping system, which can improve the electroluminescent performance of the blue light material in the aggregated state of the doped thin film. In addition to conventional doping systems, for sensitized doping systems, this type of material usually needs to introduce more steric hindrance groups to reduce the ACQ effect. The cyclohexenyl structure introduced in the present invention can synergistically exert the AIE effect with the steric hindrance group, so that the material of the present invention can also show higher device efficiency in the sensitized doping system. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention.
[0054] Description of the drawings: 1-substrate, 2-anode, 3-hole injection layer, 4-hole transport layer, 5-electron blocking layer, 6-light-emitting layer, 7-hole blocking layer, 8-electron transport layer, 9-electron injection layer, 10-cathode. DETAILED DESCRIPTION
[0055] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.
[0056] The compounds of the present invention are suitable for use in light-emitting elements, display panels and electronic devices, and are particularly suitable for use in organic electroluminescent devices. The electronic device described in the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED), an organic integrated circuit (O-IC), an organic field effect transistor (O-FET), an organic thin film transistor (O-TFT), an organic light-emitting transistor (O-LET), an organic solar cell (O-SC), an organic dye-sensitized solar cell (O-DSSC), an organic optical detector, an organic photoreceptor, an organic field quenching device (O-FQD), a light-emitting electrochemical cell (LEC), an organic laser diode (O-laser) and an organic plasma emission device. The electronic device is preferably an organic electroluminescent device (OLED). The structural schematic diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.
[0057] Experimental Section
[0058] In order to understand the content of the present invention more clearly, the polycyclic compound, the preparation method of the compound and the luminescent characteristics of the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of an embodiment of the present invention. However, it should be noted that the synthetic method of the compound of an embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.
[0059] Compound
[0060] Synthesis of Intermediate A
[0061] Intermediate A Synthesis Route:
[0062]
[0063] Taking the synthesis of A1 as an example for detailed description, the preparation route is as follows:
[0064]
[0065] Y1 (4.33 g, 0.025 mol), Q1 (6.19 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product S1: 5.83 g, yield: 70%, MS (m / z) (M+): 363.
[0066] S1 (9.05 g, 0.025 mol), T1 (6.49 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product U1: 10.64 g, yield: 82%, MS (m / z) (M+): 564.
[0067] U1 (28.15 g, 0.05 mol), V1 (6.71 g, 0.045 mol) and sodium tert-butoxide (5.28 g, 0.055 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.46 g, 0.50 mmol) and tri-tert-butylphosphine (0.26 g, 1 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product W1: 23.39 g, yield: 77%, MS (m / z) (M+): 676.
[0068] X1 (5.33 g, 0.025 mol), W1 (15.53 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product A1: 11.16 g, yield: 60%, MS (m / z) (M+): 809.
[0069] After A1 is obtained through the above process, other intermediates can be easily obtained by a method similar to A1.
[0070] BD Synthesis Example
[0071] Synthesis Example 1
[0072]
[0073] A1 (8.08 g; 10 mmol) was added to tert-butylbenzene (125 ml), then the temperature was lowered to 0°C under nitrogen protection, 12.4 ml (21 mmol) of 1.7 M n-butyl lithium pentane solution was added, the temperature was raised to 60°C and stirred for 2 hours, then the temperature was lowered to 0°C, 2.0 ml (21 mmol) of boron tribromide was added and stirred for 0.5 h, the temperature was lowered to 0°C, 3.65 ml (21 mmol) of N, N-diisopropylethylamine was added, the temperature was raised to 60°C and stirred for 2 h, ice water was added to cool to room temperature, and the mixture was separated, the organic phase was filtered and dehydrated with anhydrous magnesium sulfate, the organic solvent was removed by rotation, and the crude product was purified by recrystallization from dichloromethane and n-heptane. Finally, the product B1 was obtained: 0.47 g, yield: 6%, MS (m / z) (M+): 782.
[0074] Synthesis Example 2
[0075]
[0076] The method is the same as that of Synthesis Example 1, except that A5 (8.08 g; 10 mmol) replaces A1, and finally the product B5 is obtained: 0.39 g, yield: 5%, MS (m / z) (M+): 782.
[0077] Synthesis Example 3
[0078]
[0079] The method is the same as that of Synthesis Example 1, except that A6 (10.47 g; 10 mmol) is used to replace A1, and finally the product B6 is obtained: 0.82 g, yield: 8%, MS (m / z) (M+): 1021.
[0080] Synthesis Example 4
[0081]
[0082] The method is the same as that of Synthesis Example 1, except that A7 (10.49 g; 10 mmol) is used to replace A1, and finally the product B7 is obtained: 0.61 g, yield: 6%, MS (m / z) (M+): 1023.
[0083] Synthesis Example 5
[0084]
[0085] The method is the same as that of Synthesis Example 1, except that A8 (10.9 g; 10 mmol) is used to replace A1, and finally the product B8 is obtained: 0.85 g, yield: 8%, MS (m / z) (M+): 1064.
[0086] Synthesis Example 6
[0087]
[0088] The method is the same as that of Synthesis Example 1, except that A9 (7.8 g; 10 mmol) replaces A1, and finally the product B9 is obtained: 0.45 g, yield: 6%, MS (m / z) (M+): 754.
[0089] Synthesis Example 7
[0090]
[0091] The method is the same as that of Synthesis Example 1, except that A11 (8.12 g; 10 mmol) is used to replace A1, and finally product B11 is obtained: 0.71 g, yield: 9%, MS (m / z) (M+): 786.
[0092] Synthesis Example 8
[0093]
[0094] The method is the same as that of Synthesis Example 1, except that A12 (9.96 g; 10 mmol) is used to replace A1, and finally the product B12 is obtained: 0.78 g, yield: 8%, MS (m / z) (M+): 970.
[0095] Synthesis Example 9
[0096]
[0097] The method is the same as that of Synthesis Example 1, except that A13 (9.99 g; 10 mmol) is used to replace A1, and finally product B13 is obtained: 0.49 g, yield: 5%, MS (m / z) (M+): 973.
[0098] Synthesis Example 10
[0099]
[0100] The method is the same as that of Synthesis Example 1, except that A14 (11.02 g; 10 mmol) is used to replace A1, and finally product B14 is obtained: 0.54 g, yield: 5%, MS (m / z) (M+): 1076.
[0101] Synthesis Example 11
[0102]
[0103] The method is the same as that of Synthesis Example 1, except that A16 (11.26 g; 10 mmol) is used to replace A1, and finally product B16 is obtained: 0.99 g, yield: 9%, MS (m / z) (M+): 1100.
[0104] Synthesis Example 12
[0105]
[0106] The method is the same as that of Synthesis Example 1, except that A19 (8.08 g; 10 mmol) is used to replace A1, and finally the product B19 is obtained: 0.47 g, yield: 6%, MS (m / z) (M+): 782.
[0107] Synthesis Example 13
[0108]
[0109] The method is the same as that of Synthesis Example 1, except that A21 (10.98 g; 10 mmol) is used to replace A1, and finally the product B21 is obtained: 0.96 g, yield: 9%, MS (m / z) (M+): 1072.
[0110] Synthesis Example 14
[0111]
[0112] The method is the same as that of Synthesis Example 1, except that A22 (10.26 g; 10 mmol) replaces A1, and finally the product B22 is obtained: 0.8 g, yield: 8%, MS (m / z) (M+): 1000.
[0113] Synthesis Example 15
[0114]
[0115] The method is the same as that of Synthesis Example 1, except that A23 (11.06 g; 10 mmol) is used to replace A1, and finally the product B23 is obtained: 0.76 g, yield: 7%, MS (m / z) (M+): 1080.
[0116] Synthesis Example 16
[0117]
[0118] The method is the same as that of Synthesis Example 1, except that A24 (10.09 g; 10 mmol) is used to replace A1, and finally the product B24 is obtained: 0.79 g, yield: 8%, MS (m / z) (M+): 983.
[0119] Synthesis Example 17
[0120]
[0121] The method is the same as that of Synthesis Example 1, except that A25 (11.8 g; 10 mmol) is used to replace A1, and finally the product B25 is obtained: 0.92 g, yield: 8%, MS (m / z) (M+): 1155.
[0122] Synthesis Example 18
[0123]
[0124] The method is the same as that of Synthesis Example 1, except that A26 (10.76 g; 10 mmol) is used to replace A1, and finally the product B26 is obtained: 0.63 g, yield: 6%, MS (m / z) (M+): 1050.
[0125] Synthesis Example 19
[0126]
[0127] The method is the same as that of Synthesis Example 1, except that A27 (10.82 g; 10 mmol) is used to replace A1, and finally the product B27 is obtained: 0.84 g, yield: 8%, MS (m / z) (M+): 1056.
[0128] Synthesis Example 20
[0129]
[0130] The method is the same as that of Synthesis Example 1, except that A29 (11.03 g; 10 mmol) is used to replace A1, and finally the product B29 is obtained: 0.86 g, yield: 8%, MS (m / z) (M+): 1077.
[0131] Synthesis Example 21
[0132]
[0133] The method is the same as that of Synthesis Example 1, except that A32 (10.76 g; 10 mmol) is used to replace A1, and finally the product B32 is obtained: 0.63 g, yield: 6%, MS (m / z) (M+): 1050.
[0134] Synthesis Example 22
[0135]
[0136] The method is the same as that of Synthesis Example 1, except that A33 (10.81 g; 10 mmol) is used to replace A1, and finally the product B33 is obtained: 0.74 g, yield: 7%, MS (m / z) (M+): 1055.
[0137] Synthesis Example 23
[0138]
[0139] The method is the same as that of Synthesis Example 1, except that A35 (11.2 g; 10 mmol) is used to replace A1, and finally the product B35 is obtained: 0.77 g, yield: 7%, MS (m / z) (M+): 1094.
[0140] Synthesis Example 24
[0141]
[0142] The method is the same as that of Synthesis Example 1, except that A37 (12.98 g; 10 mmol) is used to replace A1, and finally the product B37 is obtained: 0.89 g, yield: 7%, MS (m / z) (M+): 1272.
[0143] Synthesis Example 25
[0144]
[0145] The method is the same as that of Synthesis Example 1, except that A40 (11.54 g; 10 mmol) is used to replace A1, and finally the product B40 is obtained: 0.56 g, yield: 5%, MS (m / z) (M+): 1128.
[0146] Comparative compounds
[0147]
[0148] Material properties
[0149] In order to illustrate the unique advantages of the compounds designed by the present invention, the fluorescence quantum efficiency of the compounds at different doping concentrations was tested and compared:
[0150] 1. In order to illustrate the unique advantage of the compounds of the present invention in significantly reducing the concentration quenching effect (ACQ) under the aggregation-induced emission effect (AIE), the strength of the fluorescence concentration quenching effect is measured by testing the difference in film PLQY under different guest material concentrations. Usually, since the luminescent material has a certain ACQ effect, the PLQY value usually decreases with increasing concentration, which means that the PLQY difference (PLQY difference = 1% doping concentration PLQY-3% doping concentration PLQY) is a positive value, that is, the PLQY value of a high concentration is usually less than the PLQY value of a low concentration. At this time, the AIE effect is weak or absent, and the ACQ effect is obvious. Conversely, when the difference is a negative value, it indicates that the PLQY also increases when the concentration increases. At this time, the AIE effect may be at work, which offsets the ACQ effect to a certain extent.
[0151] 2. Generally, the introduction of alkenyl groups into boron nitrogen structures will lead to a significant decrease in stability. This is because the activity of the alkenyl groups is increased when the aromatic skeleton structure of the boron nitrogen parent nucleus is connected to the alkenyl groups. In order to illustrate the improvement in stability of the alkenyl groups containing cycloalkyl structures introduced by the present invention, a thermal stability test is performed. The material of the present invention is placed at 280°C for 240 hours for a thermal stability experiment. The change in material purity before and after the thermal stability experiment is tested using a high performance liquid chromatograph. The smaller the purity change, i.e., the purity difference, the better the thermal stability of the material. As can be seen from the table below, compared with DBBD03, the thermal stability of the present invention is significantly improved, reaching a level comparable to that of conventional BD materials.
[0152] Table 1
[0153] Object material PLQY difference Purity Difference B1 -2.92 0.005 B5 -2.35 0.006 B6 -4.88 0.007 B7 -3.85 0.005 B8 -3.75 0.006 B9 -1.62 0.008 B11 -1.93 0.009 B12 -2.38 0.009 B13 -4.8 0.007 B14 -4.44 0.009 B16 -4.4 0.006 B19 -1.95 0.006 B21 -4.68 0.007 B22 -4.37 0.009 B23 -4.93 0.008 B24 -3.92 0.009 B25 -4.92 0.005 B26 -3.54 0.006 B27 -3.41 0.009 B29 -3.64 0.008 B32 -3.47 0.009 DBBD01 -0.31 0.136 DBBD02 3.24 0.049 DBBD03 4.95 2.569 B33 -1.38 0.008 B35 -2.78 0.007 B37 -4.52 0.008 B40 -4.63 0.007 DBBD04 3.94 0.126
[0154] Note: The fluorescence quantum efficiency (PLQY) is the material co-evaporated on a high-transparency quartz glass sheet by dual sources. The concentration of the guest material is 1% and 3% of the total mass, respectively, and the film thickness is 20nm. It is tested using Horiba's Fluorolog-3 series fluorescence spectrometer (integrating sphere).
[0155] It can be seen from the above table that the material structure of the present invention has a more obvious AIE effect, and the purity decreases less. This is the effect brought about by the combination of the olefin-containing cycloalkyl fragment introduced by the present invention and the boron nitrogen structure; in particular, compared with the multi-linked carbazole group used in DBBD01, the characteristic group introduced by the present invention has a more significant AIE effect. This is because the substituted olefin group is compared with the aromatic amine, due to the non-free rotation of the double bond, so that the spatial distortion steric effect brought by the substituent is more significant, and the restriction on the freely rotatable and vibrating fragments in the aggregated state is greater, so that the exciton energy cannot be dissipated through dark state modes such as vibration relaxation, internal conversion, and non-radiative transition, thereby improving the luminescence in the aggregated state. DBBD03 and the like only have olefin groups, not only have no significant AIE effect, but also have poor stability, which will seriously affect the lifespan. The groups introduced into the material of the present invention do not cause serious decomposition and degradation of the material of the present invention during the thermal stabilization process. Therefore, the stability performance of the present invention is at a comparable level with other comparative examples, and has good stability.
[0156] Fabrication and characterization of OLEDs
[0157] Device Embodiment
[0158] The organic electroluminescent device provided by the present invention comprises an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode which are sequentially arranged on a substrate;
[0159] Furthermore, the hole transport region includes a hole injection layer, a hole transport layer and a light-emitting auxiliary layer; and the electron transport region includes an electron transport layer and an electron injection layer.
[0160] Furthermore, the light-emitting layer is composed of a host material and a guest material, and the host material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.
[0161] The composition of the present invention can be used for the light-emitting layer of the above-mentioned organic electroluminescent device.
[0162] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts the host and guest material composition provided by the present invention. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).
[0163] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:
[0164] Blue light device embodiment 1
[0165] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr. Then the following operations were performed: first, on the ITO layer (anode) formed on the substrate, HT01 and PD01 (the mass ratio of HT01 to PD01 was 97:3) were vacuum deposited with a thickness of 10 nm to form a hole injection layer; secondly, on the hole injection layer, HT01 was vacuum deposited with a thickness of 120 nm to form a hole transport layer; secondly, on the hole transport layer, BP01 was vacuum deposited with a thickness of 5 nm to form an electron blocking layer; secondly, on the electron blocking layer, a mixture of BH01 and B1 provided by the present invention was vacuum deposited with a thickness of 20 nm to form a light-emitting layer, wherein BH01 was used as a host material and B1 was used as a guest material, and the mass ratio of the host material to the guest material was 98:2; then, on the light-emitting layer, HB01 was vacuum deposited with a thickness of 5 nm to form a hole blocking layer; then, on the hole blocking layer, , ET01:LiQ (the mass ratio of ET01 to LiQ is 1:1) is vacuum deposited with a thickness of 20nm to form an electron transport layer; then Yb is vacuum deposited with a thickness of 1nm on the above electron transport layer to form an electron injection layer, and then Mg:Ag (the mass ratio of Mg and Ag is 1:9) is deposited with a thickness of 15nm on the above electron injection layer to form a cathode, and then CPL01 is deposited with a thickness of 50nm on the above cathode to form a covering layer, finally, the evaporated substrate is packaged, the cleaned cover plate is coated with UV glue using a glue coating equipment, and then the coated cover plate is moved to the pressing section, the evaporated substrate is placed on the upper end of the cover plate, and finally the substrate and the cover plate are bonded under the action of the bonding equipment, and the UV glue is light-cured at the same time to prepare a laminated organic electroluminescent device.
[0166] Except for the guest material of the light-emitting layer, the molecular structures of the materials in the remaining layers are as follows:
[0167]
[0168] Blue light device embodiment 2-21
[0169] The above method was used to prepare organic electroluminescent devices from the compounds described in other examples in Table 2, and blue organic electroluminescent device examples 2-21 were prepared by replacing B1 in device example 1 with the guest materials shown in the examples in Table 2.
[0170] Comparative Examples 1-3 of Blue Light Devices
[0171] The above method was used to prepare organic electroluminescent devices from the compounds described in the comparative examples in Table 2, and the guest materials shown in the comparative examples in Table 2 were used to replace B1 in device example 1 to prepare blue light organic electroluminescent device comparative examples 1-3.
[0172] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage and luminous efficiency of the organic electroluminescent device are determined at a current density of J = 20 mA / cm 2 When working under LT95, the luminous brightness drops to 95% of its initial value L0 after time LT95.
[0173] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:
[0174] The luminous efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;
[0175] Current density and lighting voltage: tested using a digital source meter Keithley 2400;
[0176] The luminous efficiency of blue light devices is greatly affected by chromaticity. The industry generally uses BI value as the basis for the efficiency of blue light devices. BI (Blue index) is obtained by dividing the luminous efficiency CE (cd / A) by the color coordinate (CIEy);
[0177] Life test: Use silicon photoelectric OLED device life test system.
[0178] The performance test results of the above devices are listed in Table 2.
[0179] Table 2 Blue light device performance test results
[0180]
[0181]
[0182] It can be seen from the device performance test results in Table 2 above that the device containing the composition of the present invention has a significant advantage in luminescence performance, which just shows that the use of the compound of the present invention has a significant improvement in device efficiency, which is consistent with the effect example, indicating that the doped molecules in the aggregated state in the film still have an AIE effect in the complex structure of the device, so that the device efficiency is significantly improved. At the same time, the introduction of the alkenyl group in the present invention does not cause a significant increase in structural instability, so the lifespan has a better performance, and the lifespan is at a better level compared with the comparative example.
[0183] Sensitized blue light device embodiment 1
[0184] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr. Then the following operations were performed: first, HT01 and PD01 (the mass ratio of HT01 to PD01 was 97:3) were vacuum deposited on the ITO layer (anode) formed on the substrate with a thickness of 10 nm to form a hole injection layer; secondly, HT01 was vacuum deposited on the hole injection layer with a thickness of 120 nm to form a hole transport layer; secondly, BP01 was vacuum deposited on the hole transport layer with a thickness of 5 nm to form an electron blocking layer; and thirdly, a mixture of BH02, BH03, PBD01 and B33 provided by the present invention was vacuum deposited on the electron blocking layer with a thickness of 20 nm to form a light-emitting layer, wherein BH02 and BH03 were used as the main body and PB D01 is used as a sensitizer and B33 is used as a guest material. The mass ratio of BH02, BH03, PBD01 and B33 is 42.5:42.5:14:1. Then, HB01 is vacuum deposited on the light-emitting layer with a thickness of 10 nm to form a hole blocking layer. Then, ET01:LiQ (the ratio of ET01 to LiQ is 1:1) is vacuum deposited on the hole blocking layer with a thickness of 20 nm to form an electron transport layer. Then, Yb is vacuum deposited on the electron transport layer with a thickness of 1 nm to form an electron injection layer. Then, Al is deposited on the electron injection layer with a thickness of 300 nm to form a cathode, thereby completing the manufacture of an organic light-emitting device.
[0185] Except for the guest material of the light-emitting layer, the molecular structures of the materials in the remaining layers are as follows:
[0186]
[0187] Sensitized blue light device examples 2-4
[0188] The above method was used to prepare organic electroluminescent devices from the compounds described in other examples in Table 3, and the guest materials shown in the examples in Table 3 were used to replace B33 in the sensitized blue light device example 1 to prepare sensitized blue light device examples 2-4.
[0189] Sensitized blue light device comparative example 1
[0190] The above method was used to prepare the organic electroluminescent device from the compound described in the comparative example in Table 3, and the guest material DBBD04 shown in the comparative example in Table 3 was used to replace B33 in the sensitized blue light device example 1 to prepare the sensitized blue light device comparative example 1.
[0191] The test conditions refer to the above-mentioned blue light device, and the results are shown in Table 3.
[0192] Table 3
[0193] Sensitized blue light device Object material Volt(V) BI(cd / A / CIEy) LT95(h) Sensitized blue light device embodiment 1 B33 3.86 221.7 305 Sensitized blue light device embodiment 2 B35 3.93 229.5 283 Sensitized blue light device embodiment 3 B37 3.97 235.3 297 Sensitized blue light device embodiment 4 B40 3.91 233.4 306 Sensitized blue light device comparative example 1 DBBD04 4.12 205.6 164
[0194] It can be seen from Table 3 that B33, B35, B37, B40 and DBBD04 have more steric hindering groups such as carbazole and biphenyl in their structures, and are suitable as guest materials for sensitized blue light devices. It can also be seen that the materials of the present invention still have obvious improvement in luminous efficiency compared with the comparative examples.
[0195] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A blue light-emitting compound containing a cyclohexenyl group, characterized in that: The blue light-emitting compound is as shown in Formula I; wherein Ring A represents any one of a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, and a substituted or unsubstituted heteroaryl group having 5 to 30 carbon atoms; R1-R5 each independently represents any one of a methyl group, an ethyl group, a propyl group, an isopropyl group, a tert-butyl group, a cycloalkyl group, a cyclohexenyl group, a diamino group, a cyclohexenyl-substituted diamino group or a carbazole group, and at least one of R1-R5 represents a cyclohexenyl structure shown in one of A1 to A3 below, and adjacent R2 groups may be bonded to each other via a linking group or a single bond to form an aromatic ring or a condensed ring; R6 represents hydrogen or methyl; L1-L3 each independently represent any one of a single bond, a substituted or unsubstituted arylene group, a substituted or unsubstituted arylene group connected in a ring, and a substituted or unsubstituted arylene group connected in a heterocyclic ring; m, n, o, p, q each independently represent 0, 1, 2 or 3. When m, n, o, p, q represent 2 or 3, R1-R5 may be the same or different; In Formula I, any hydrogen may be replaced by deuterium, and any nitrogen may be replaced by 15 N substitution, any sulfur can be 33 S. 34 S or 36 S substitution, any oxygen can be 17 O or 18 O substitution, any carbon can be 13 C substitution, any boron can be 11 B replaced.
2. The blue luminescent compound according to claim 1, characterized in that: At least one of R3 and R5 is selected from one of the cyclohexenyl structures shown in A1 to A3.
3. The blue luminescent compound according to claim 1, characterized in that The blue light-emitting compound is selected from the structure shown in Formula II or Formula III:
4. The blue luminescent compound according to claim 3, characterized in that: The compound represented by formula II is selected from the structure represented by one of formula II-1 to formula II-7: m1, m5, and m6 each independently represent an integer from 0 to 5, and m2, m3, m4, and m7 each independently represent an integer from 0 to 8; n1, n2, n5, n6, and n7 each independently represent an integer from 0 to 5, and n3 and n4 each independently represent an integer from 0 to 8; R 11 , R 21 , R4 each independently represents hydrogen or an alkyl group having 1 to 5 carbon atoms; at least one of R3 and R5 is a cyclohexenyl structure represented by one of A1 to A3.
5. The blue luminescent compound according to claim 4, characterized in that: The R 11 , R 21 Represents hydrogen.
6. The blue luminescent compound according to claim 3, characterized in that: The compound represented by formula III is selected from the structure represented by one of formulas III-1 to III-4: R7 and R8 each independently represent any one of an alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, a substituted or unsubstituted cyclohexenyl group, and a substituted or unsubstituted dibenzofuranyl group; n8 represents an integer from 0 to 4.
7. The blue light-emitting compound according to claim 1, characterized in that: The arylene group is selected from any one of phenylene, biphenylene and terphenylene; The arylene group connected in a ring is selected from any one of fluorenylene and spirofluorenylene; The arylene group connected with the heterocyclic ring is selected from any one of dibenzofuranyl and diarylamine.
8. The blue light-emitting compound according to claim 1, characterized in that: The blue light-emitting compound is selected from one of the following structures:
9. An organic electroluminescent device, characterized in that: It comprises an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode which are sequentially arranged on a substrate; wherein the light-emitting layer comprises one or more blue light-emitting compounds as described in any one of claims 1 to 8.
10. The organic electroluminescent device according to claim 9, characterized in that: The light-emitting layer comprises a host material and a guest material, wherein the guest material comprises one or more blue light-emitting compounds according to any one of claims 1 to 8.